Use of Freire's Conscientization in Mathematics Learning - Roka, Jasbir (Academic Journal of Mathematics Education, 2023)
Conscientization in mathematics refers to the process by which students develop a critical awareness of the world view through education with their life experiences in mathematics learning. This qualitative study to analyze the use of Freire's conscientization in mathematics learning. The information was collected through secondary data as research articles, archival documents related with reliable sources. The conclusion showed that by using Freire's conscientization students develop a critical awareness of the world through education with their real-life experiences in mathematics. It advocated critical pedagogy in which teachers and students learn together through dialogue and it always welcomes critical analysis in the mathematics learning. The study has implication in mathematics learning, students share their experiences with other classmates in small groups as contextual teaching strategies in mathematics. It is recommended that a new relationship between teachers and students as well as society for an effective mathematics teaching strategy should be developed.